Water-based composite electrolyte containing charge-separated inner salt additive and preparation method and application of water-based composite electrolyte

By using charge-separated internal salt additives in aqueous zinc ion batteries, the zinc ion solvation structure and interface double layer are adjusted to form a solid electrolyte interface, which solves the problem of uneven interface impedance and deposition of zinc negative electrodes, and significantly improves the battery cyclic performance and reversibility.

CN119208768APending Publication Date: 2024-12-27CHANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411350062.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In aqueous zinc ion batteries, due to the acidity of zinc sulfate electrolyte and the high reactivity of water molecules, the interface impedance of zinc negative electrode increases, uneven zinc deposition and corrosion of active metal zinc, which reduces the effective utilization rate of zinc negative electrode and has a high concentration. The addition of salt will lead to excessive viscosity of the electrolyte and a decrease in ionic conductivity, affecting battery performance.

Method used

Using charge-separated internal salt additives, adjust the interface electric double layer between zinc ion solvation structure and zinc negative electrode, so that additive molecules are enriched on the surface of zinc negative electrode, decompose to form a solid electrolyte interface, inhibit dendritic growth and interface side reactions, and reduce electrolysis The concentration of salt in the liquid.

Benefits of technology

Through the charge-separated internal salt additive, the directional migration and diffusion of zinc ions is improved, the cycling performance of the battery under large currents is improved, and the stable circulation is 520 hours, which reduces the hydrogen evolution side reaction, increases the zinc deposition overpotential, and forms a more uniform The electrode surface significantly improves the reversibility and cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208768A_ABST
    Figure CN119208768A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of water-based zinc ion batteries, in particular to a water-based composite electrolyte containing a charge separation inner salt additive and a preparation method and application of the water-based composite electrolyte. An inner salt additive containing charge separation is added into a zinc ion electrolyte to prepare a water-based composite electrolyte, and the water-based composite electrolyte is applied to a zinc battery. The inner salt additive for charge separation changes the solvation structure of zinc ions through the chelation with the zinc ions, and attracts the zinc negative electrode through the charge effect to enrich on the surface of the zinc negative electrode to generate a solid electrolyte interface in situ, so that the diffusion mode of the zinc ions at the interface of the zinc negative electrode is changed from two-dimensional diffusion to three-dimensional diffusion; the formation and growth of zinc dendrites are inhibited, and the coulombic efficiency of the battery and the cycle performance of the battery under high current are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aqueous zinc ion batteries, and in particular to an aqueous composite electrolyte containing an inner salt additive for charge separation, and a preparation method and application thereof. Background Art

[0002] As renewable energy sources become an increasing share of the energy mix, there is a growing demand for large-scale battery energy storage to balance the grid and store excess energy. Lithium-ion batteries currently dominate the battery technology market. However, long-standing concerns about the sustainability and safety of lithium-ion batteries have prompted research into alternative battery chemistries. Zinc-ion batteries have been used for a long time due to their high theoretical capacity (820 mAh / g, 5854 mAh / cm 2 ), low redox potential (-0.763V vs SHE), non-toxic, abundant reserves, reasonable price, and environmentally friendly, have attracted widespread attention.

[0003] Among the various available zinc salts, zinc sulfate salts are favored due to their cost-effectiveness, non-toxicity, and low corrosiveness, making them the standard electrolyte commonly used in aqueous zinc-ion batteries. However, the inherent acidity of zinc sulfate electrolyte and the high reactivity of water molecules induce inevitable side reactions and the formation of inactive species on the surface of the zinc anode, resulting in increased interfacial impedance and uneven zinc deposition. In addition, OH produced by water decomposition - The anions change the local pH environment, leading to the corrosion and depletion of active metallic zinc, thus reducing the effective utilization of the zinc anode.

[0004] Studies have shown that by using additives containing electron-rich groups to adjust the solvation sheath structure of zinc ions, the content of active water at the zinc negative electrode interface can be effectively reduced. In addition, this method can also adjust the interfacial chemical properties of the solid electrolyte interface derived from electron-rich groups, making it chemically uniform and mechanically robust. In the past, in order to obtain a solid electrolyte interface with good performance, high concentrations of salt were usually used to affect the formation of the solid electrolyte interface by changing the solvation structure of zinc ions. However, adding too much salt will cause the viscosity of the electrolyte to be too high, and the decrease in ionic conductivity will have an adverse effect on the ion transport kinetics, thereby further damaging the overall performance of the battery. Moreover, the addition of too many additives will also lead to increased costs.

[0005] In order to solve this problem, additives with low LOMO energy levels are introduced to preferentially decompose at the zinc anode interface to form a solid electrolyte interface, thereby reducing the salt concentration in the electrolyte. Currently, there are few reports on solid electrolyte interfaces in zinc sulfate electrolyte systems. Summary of the invention

[0006] In view of the deficiencies pointed out in the above background technology, the present invention uses charge-separated internal salt additives to adjust the zinc ion solvation structure and the zinc negative electrode interface double layer, so that the additive molecules are enriched on the zinc negative electrode surface, promoting their decomposition to form a solid electrolyte interface, and effectively inhibiting dendrite growth and interface side reactions.

[0007] In order to achieve the above object, the present invention provides an aqueous composite electrolyte containing a charge-separated inner salt additive, which consists of a charge-separated inner salt additive, a soluble zinc salt, and water.

[0008] According to one aspect of the present invention, the soluble zinc salt is selected from zinc sulfate, zinc chloride, zinc nitrate, zinc acetate, zinc trifluoromethanesulfonate, zinc perchlorate, zinc trifluoromethanesulfonyl imide, zinc tetrafluoroborate, or a combination of two or more thereof. In the present invention, the soluble zinc salt is preferably zinc sulfate.

[0009] According to one aspect of the present invention, the concentration of the soluble zinc salt in the aqueous zinc salt electrolyte is 0.2-4 mol / kg. The preferred concentration of the soluble zinc salt in the present invention is 3 mol / kg.

[0010] According to one aspect of the present invention, the charge-separated inner salt additive is one or more of trigonelline, 1,3-dimethylimidazolium-2-carboxylate, 3-(benzyldimethylammonium)propane sulfonic acid, 3-(triphenylphosphine)propane-1-sulfonate, propane sulfonate pyridinium salt, nitrate, 3-[dimethyl-(2-hydroxyethyl)ammonium]-1-propane sulfonate, N,N-dihydroxyethylglycine and trimethylammonium betaine.

[0011] According to one aspect of the present invention, in the aqueous composite electrolyte containing the charge-separating inner salt additive, the concentration of the charge-separating inner salt additive is 0.2-5 mol / kg, preferably 1-3 mol / kg.

[0012] The method for preparing the aqueous composite electrolyte containing the charge-separating inner salt additive comprises the following steps:

[0013] Adding soluble zinc salt into deionized water to prepare an aqueous zinc salt electrolyte;

[0014] Take the prepared aqueous zinc salt electrolyte, add the charge-separated inner salt additive, continue stirring until it is completely dissolved, and then let it stand to obtain an aqueous composite electrolyte containing the charge-separated inner salt additive.

[0015] The invention also discloses a battery comprising the aqueous composite electrolyte containing the charge-separating internal salt additive.

[0016] According to one aspect of the present invention, the battery includes a symmetrical battery assembled from commercial zinc sheets, a half-cell assembled from commercial current collectors, and an aqueous zinc ion battery assembled from commercial zinc sheets as negative electrodes and metal oxides as positive electrodes.

[0017] According to one aspect of the present invention, the metal oxide comprises MnO2, NH4V4O 10 , V2O5 or VO2.

[0018] According to one aspect of the present invention, the commercial current collector is selected from any one of titanium foil, copper foil, nickel foil, stainless steel mesh, copper mesh, nickel mesh, foam copper and foam nickel.

[0019] The invention has the advantages that: the invention adds an inner salt additive containing charge separation in the electrolyte, and the inner salt additive of charge separation changes the solvation structure of zinc ions by chelating with zinc ions, and attracts each other with the zinc negative electrode through charge action, which is conducive to the directional migration of zinc ions. Meanwhile, the inner salt additive of charge separation that is not free with zinc ion coordination in the electrolyte participates in the regulation of the double electric layer at the zinc negative electrode interface by virtue of its zinc affinity. The regulation of the double electric layer by the inner salt additive of charge separation not only makes the inner salt additive molecules of charge separation enriched on the zinc negative electrode surface, but also affects the zinc ion desolvation process. Under the synergistic effect of the two, the inner salt additive molecules of active charge separation participating in the coordination of the zinc ion solvation sheath and the inner salt additive molecules of charge separation that are not involved in coordination in the electrolyte are prompted to react at the interface to generate a solid electrolyte interface in situ. The change of the zinc ion solvation structure and the regulation of the double electric layer by the internal salt additive molecules improve the diffusion mode of zinc ions at the zinc negative electrode interface, changing from two-dimensional diffusion to three-dimensional diffusion, promoting the uniform migration and deposition of zinc ions on the negative electrode surface, thereby inhibiting the formation and growth of zinc dendrites. The directional migration and diffusion mode of zinc ions greatly improve the cycle performance of the battery under high current. 2 -5 mAh / cm 2 Under the condition of , it can stably circulate for about 520 hours. The effect is obviously better than the current small molecule organic matter and polymer additives.

[0020] The beneficial effects of the present invention are:

[0021] (1) The electrolyte is modified by charge-separating internal salt additives, which has low preparation cost and simple preparation method and is suitable for large-scale production.

[0022] (2) The charge-separated internal salt additive introduced into the electrolyte of the present invention regulates the hydrogen bond network in the double electric layer at the interface of the zinc negative electrode, effectively reduces the hydrogen evolution side reaction, and improves the reversibility of the zinc negative electrode.

[0023] (3) The charge-separated inner salt additive molecules coordinate with the zinc ions in the electrolyte through chelation with the zinc ions, and attract each other with the zinc negative electrode through charge interaction, which is beneficial to the directional migration of zinc ions.

[0024] (4) The charge-separated inner salt additive molecules reduce the amount of coordinated water in the solvation sheath structure of the zinc ions by chelating with them, thereby increasing the zinc deposition overpotential and allowing zinc to be deposited in smaller grains and more evenly on the electrode surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The zinc-zinc symmetric battery prepared by the electrolyte (TE) and zinc sulfate aqueous solution (ZSO) containing different concentrations of charge separation provided in Example 1 has a current of 1 mA / cm 2 Time-voltage curve under current density

[0026] Figure 2 Scanning electron microscope image of the cross section of the zinc negative electrode of the zinc-vanadium dioxide full battery after cycling, prepared from the charge-separated inner salt additive electrolyte provided in Example 1.

[0027] Figure 3 XRD spectrum of the zinc negative electrode surface of the zinc-vanadium dioxide full battery prepared with the charge-separated inner salt additive electrolyte provided in Example 1 after 10 cycles.

[0028] Figure 4 Impedance test of a zinc-vanadium dioxide full cell prepared from the charge-separated inner salt additive electrolyte (TE) and zinc sulfate aqueous solution (ZSO) provided in Example 1.

[0029] Figure 5 Impedance test of the zinc-vanadium dioxide full battery containing the charge-separated internal salt additive electrolyte provided in Example 1 after 10 cycles.

[0030] Figure 6 The zinc-zinc symmetric battery prepared by the charge-separated inner salt additive electrolyte (TE) and zinc sulfate aqueous solution (ZSO) provided in Example 1 has a current of 5 mA / cm 2 Time-voltage curves at different current densities.

[0031] Figure 7 Coulombic efficiency curve of a zinc-copper asymmetric battery prepared with the charge-separated inner salt additive electrolyte (TE) and zinc sulfate aqueous solution (ZSO) provided in Example 1, and voltage-capacity curves at 200, 800, 1600 and 3800 cycles.

[0032] Figure 8Chronoamperometric curve of a zinc-zinc symmetric battery prepared from the charge-separated inner salt additive electrolyte (TE) and zinc sulfate aqueous solution (ZSO) provided in Example 1.

[0033] Fig. 9 The time-voltage curves of zinc-zinc symmetric batteries prepared from electrolytes containing different charge-separating inner salt additives and zinc sulfate aqueous solution (ZSO) provided in Example 2.

[0034] Fig.10 Coulomb efficiency curves of zinc-copper asymmetric batteries prepared with electrolytes containing different charge-separating internal salt additives and zinc sulfate aqueous solution (ZSO) provided in Example 2.

[0035] Fig.11 Scanning electron micrographs of the zinc negative electrode surface after cycling of the electrolyte containing different charge-separating inner salt additives and the zinc sulfate aqueous solution (ZSO) provided in Example 3, wherein a is zinc sulfate aqueous solution (ZSO), b is propane pyridinium sulfonate, c is N,N-dihydroxyethylglycine, d is 1,3-dimethylimidazolium-2-carboxylate, and e is trimethylammonium betaine. DETAILED DESCRIPTION

[0036] To make the present invention easier to understand, the present invention is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. Unless otherwise defined, the professional terms used below are consistent with the meanings understood by professional and technical personnel in the field; unless otherwise specified, the raw materials and reagents involved in this article can be purchased from the market or prepared by known methods.

[0037] Among them, "ZSO" in the drawings of the present application is an aqueous solution of zinc sulfate; "3mZSO" in the drawings of the present application is an aqueous solution of zinc sulfate, and the concentration of zinc sulfate salt is 3m (m:mol / kg); "TE" in the drawings of the present application is an aqueous composite electrolyte of a charge-separated inner salt additive, and the charge-separated inner salt additive is fenugreek alkaloids; "1mTE" in the drawings of the present application is an aqueous composite electrolyte of a charge-separated inner salt additive, and the charge-separated inner salt additive is fenugreek alkaloids, and the concentration of fenugreek alkaloids is 1 mol / kg.

[0038] Embodiment 1:

[0039] The aqueous zinc ion battery electrolyte of this example is specifically composed of chromatographic water, zinc sulfate and trigonelline. Its preparation method is as follows: weigh 0.53841g of zinc sulfate monohydrate, place it in 0.946g of chromatographic water, and ultrasonicate at room temperature for 20min to obtain a 3m (m: mol / kg) zinc sulfate solution. By weighing 0.013714g, 0.027428g, 0.06857g, 0.13714g, 0.41142g and 0.6857g of trigonelline, and adding it to the prepared 3m zinc sulfate solution, ultrasonicate at room temperature for 30min, a modified electrolyte containing 0.1m, 0.2m, 0.5m, 1m, 3m and 5m trigonelline additives is obtained.

[0040] The electrolytes containing different concentrations of charge-separating inner salt additives and the electrolytes without charge-separating inner salt additives obtained in this example were applied to zinc-zinc symmetrical batteries for constant current charge-discharge tests at a current density of 1 mA / cm 2 , time is 1h, observe the voltage curve.

[0041] The results are as follows Figure 1 As shown in the figure, under the condition of lower concentration of charge-separated inner salt additive, the additive molecules cannot effectively decompose on the surface of zinc negative electrode to form an effective protective layer, resulting in limited improvement of battery cycle life. Under the condition of high concentration of charge-separated inner salt additive, the viscosity of the electrolyte increases and the conductivity decreases. In addition, the charge-separated inner salt additive molecules continue to decompose on the surface of zinc negative electrode, and the solid electrolyte interface is too thick, resulting in increasing polarization of the battery until the battery short circuits. Therefore, it is crucial to adjust the concentration of the additive to obtain a solid electrolyte interface of appropriate thickness for the reversibility of the zinc negative electrode.

[0042] The electrolyte (1 m) containing the charge-separated inner salt additive obtained in this example was applied to a zinc-vanadium dioxide full battery and charged and discharged at a current of 0.1 A / g. After 10 charge and discharge cycles, the surface of the zinc electrode was observed using a scanning electron microscope.

[0043] Figure 2 This is a scanning electron microscope image of the zinc negative electrode of the zinc ion battery electrolyte containing the charge-separated inner salt additive. The results show that the surface of the zinc sheet is dense, flat and uniform, and there is no obvious dendrite, which shows that the charge-separated inner salt additive can form a solid electrolyte interface in situ on the surface of the zinc negative electrode, and effectively protect the zinc negative electrode and inhibit the growth of dendrites.

[0044] The electrolyte containing the charge-separated inner salt additive obtained in this example was applied to a zinc-vanadium dioxide full battery and charged and discharged at a current of 0.1 A / g. After 10 charge and discharge cycles, the battery was disassembled to obtain the zinc negative electrode, and the surface composition of the zinc was analyzed by XRD testing.

[0045] The results are as follows Figure 3 As shown in the figure, by comparing the corresponding PDF cards, it is found that the solid electrolyte interface formed on the surface of the zinc negative electrode after cycling is a composite SEI layer rich in carbon, nitrogen and oxygen elements. This composite interface layer can effectively improve the performance of aqueous zinc ion batteries.

[0046] The electrolyte containing the charge-separating inner salt additive and the electrolyte not containing the charge-separating inner salt additive obtained in this example were applied to zinc-vanadium dioxide full batteries, and were charged and discharged at a current of 0.1 A / g. After 30 charge and discharge cycles, impedance testing was performed.

[0047] The results are as follows Figure 4 and Figure 5 As shown in Figure 2, no SEI is formed on the zinc electrode in the initial state before cycling. The battery with the charge-separating internal salt additive electrolyte exhibits lower charge transfer resistance. After 10 cycles of zinc plating / stripping, an SEI layer is formed in the battery with the charge-separating internal salt additive electrolyte, as shown in Figure 2. Figure 5 The first semicircle in the high-frequency range corresponds to the interfacial resistance of Zn ion flux through SEI (RSEI), and the second semicircle in the low-frequency range corresponds to Rct.

[0048] The electrolyte containing the charge-separating inner salt additive and the electrolyte without the charge-separating inner salt additive obtained in this example were applied to a zinc-copper asymmetric battery to perform a coulombic efficiency test at a voltage of 0.5 V and a current density of 2 mA / cm 2 , time is 15 minutes.

[0049] The electrolyte containing the charge-separating inner salt additive and the electrolyte without the charge-separating inner salt additive obtained in this example were applied to a zinc-zinc symmetrical battery for constant current charge-discharge test at a current density of 5 mA / cm 2 , time is 1h, observe the voltage curve.

[0050] The results are as follows Figure 6 As shown, the zinc-zinc symmetric battery containing the charge-separated inner salt additive zinc ion battery electrolyte has a longer cycle life, which indicates that the charge-separated inner salt additive molecule also has excellent performance under high current conditions.

[0051] The results are as follows Figure 7 As shown in the figure, after adding the charge-separating inner salt additive, the number of cycles of the battery increased from about 300 to 5000, and the average coulombic efficiency was as high as 99.9%. This shows that adding the charge-separating inner salt additive can improve the reversibility of the zinc negative electrode.

[0052] The electrolyte containing the charge-separating inner salt additive and the electrolyte not containing the charge-separating inner salt additive obtained in this example were applied to a zinc-zinc symmetric battery, and a chronoamperometric curve at a fixed overpotential of -150 mV was obtained on an electrochemical workstation.

[0053] The results are as follows Figure 8 As shown, it can be clearly observed that the current density of zinc electrodeposition in the electrolyte before the addition of the charge-separating inner salt additive continues to increase. This trend can be attributed to the "tip effect" caused by the inhomogeneous electric field. Subsequently, zinc deposition occurs at the tip of the original irregular crystal nucleus, minimizing the surface energy and ultimately initiating the formation of uncontrollable dendrites. In contrast, in the electrolyte after the charge-separating inner salt additive is added, the current response of zinc electrodeposition remains stable after a transient increase in current density for 12 seconds. This behavior can be attributed to limited two-dimensional diffusion, which promotes the formation of a uniform and dense zinc deposition layer.

[0054] Embodiment 2:

[0055] The aqueous zinc ion battery electrolyte of this example is specifically composed of chromatographic water, 1,3-dimethylimidazolium-2-carboxylate, 3-(triphenylphosphine) propane-1-sulfonate, propanesulfonic acid pyridinium salt, nitrate, 3-[dimethyl-(2-hydroxyethyl) ammonium]-1-propanesulfonate, N,N-dihydroxyethylglycine and trimethylammonium ethyl lactone. The preparation method is as follows: weigh 0.53841g of zinc sulfate monohydrate, place it in 0.946g of chromatographic water, and ultrasonicate at room temperature for 20min to obtain a 3m (m: mol / kg) zinc sulfate solution. By weighing different masses of 1,3-dimethylimidazolium-2-carboxylate, 3-(triphenylphosphine) propane-1-sulfonate, propanesulfonic acid pyridinium salt, nitrate, 3-[dimethyl-(2-hydroxyethyl) ammonium]-1-propanesulfonate, N,N-dihydroxyethylglycine and trimethylammonium ethyl lactone respectively. The electrolyte was added into the prepared 3 m ZSO solution and ultrasonicated at room temperature for 30 min to obtain a modified electrolyte containing 1 m inner salt additive containing charge separation.

[0056] The electrolytes with different concentrations of additives prepared by the inner salt additives containing different charge separation and the electrolytes without the inner salt additives containing charge separation were applied to the zinc-zinc symmetric battery for constant current charge and discharge test. The current density was 2 mA / cm 2 , time is 0.25h, observe the voltage curve.

[0057] The results are as follows Fig. 9 As shown, the zinc-zinc symmetric battery containing the charge-separating internal salt additive zinc ion battery electrolyte has a longer cycle life.

[0058] The electrolytes with different concentrations of additives prepared by the inner salt additives containing different charge separations and the electrolytes without the inner salt additives containing charge separations obtained in this example were applied to zinc-copper asymmetric batteries to carry out coulombic efficiency tests.

[0059] The results are as follows Fig.10 This indicates that the zinc-copper asymmetric battery containing a charge-separated internal salt additive zinc ion battery electrolyte has a higher reversibility of the zinc negative electrode.

[0060] The electrolytes with different concentrations of additives prepared by the inner salt additives containing different charge separations and the electrolytes without the inner salt additives containing charge separations obtained in this example were applied to zinc-vanadium dioxide full batteries to test the cycle stability of the full batteries.

[0061] The results are shown in Table 1. The capacity retention rate of the zinc-vanadium dioxide full battery containing the charge-separated internal salt additive is higher.

[0062] Table 1

[0063]

[0064] Embodiment 3:

[0065] The aqueous zinc ion battery electrolyte of this example is specifically composed of chromatographic water, 1,3-dimethylimidazolium-2-carboxylate, trimethylammonium ethyl lactone, propane sulfonate pyridinium salt and N,N-dihydroxyethyl glycine. The preparation method is as follows: weigh 0.53841g of zinc sulfate monohydrate, place it in 0.946g of chromatographic water, and ultrasonicate at room temperature for 20min to obtain a 3m (m: mol / kg) zinc sulfate solution. By weighing different masses of 1,3-dimethylimidazolium-2-carboxylate, trimethylammonium ethyl lactone, propane sulfonate pyridinium salt and N,N-dihydroxyethyl glycine respectively. And add it to the prepared 3m ZSO solution, ultrasonicate at room temperature for 30min, and obtain a modified electrolyte containing 1m of charge-separated inner salt additive.

[0066] The electrolytes with different concentrations of additives prepared by containing internal salt additives with different charge separations and the electrolytes without internal salt additives with charge separation obtained in this example were applied to zinc-vanadium dioxide full batteries, and were charged and discharged at a current of 0.1 A / g. After 10 charge and discharge cycles, the surface of the zinc electrode was observed using a scanning electron microscope.

[0067] The results are as follows Fig.11As shown in the figure, the zinc deposition on the surface of the zinc negative electrode without charge separation inner salt additives is disorderly. In the scanning electron microscope images of the zinc negative electrode surface with different charge separation inner salt additives, the formation of the solid electrolyte interface layer can be clearly observed, and the solid electrolyte interface morphology on the surface of different charge separation inner salt additives is quite different. The symmetrical battery with dense surface solid electrolyte interface has a significantly longer cycle life ( Fig. 9 ), the average Coulombic efficiency is higher (Table 2).

[0068] Table 2

[0069] additive Number of cycles (circles) Average Coulombic efficiency (%) 1,3-Dimethylimidazolium-2-carboxylate 1200 99.81 Betaine 1200 99.74 Propane sulfonate pyridinium salt 1200 99.47 N,N-Dihydroxyethylglycine 1200 99.32

[0070] (The average coulomb efficiency data is from Fig. 9 Statistical calculation results)

[0071] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. An aqueous composite electrolyte containing an inner salt additive for charge separation, characterized in that: It is composed of a charge-separated inner salt additive, a soluble zinc salt, and water; The charge-separated inner salt additive is one or more of trigonelline, 1,3-dimethylimidazolium-2-carboxylate, 3-(benzyldimethylammonium)propane sulfonic acid, 3-(triphenylphosphine)propane-1-sulfonate, propane sulfonate pyridinium salt, nitrate, 3-[dimethyl-(2-hydroxyethyl)ammonium]-1-propane sulfonate, N,N-dihydroxyethylglycine and trimethylammonium betaine.

2. The aqueous composite electrolyte containing a charge-separating inner salt additive according to claim 1, characterized in that: The soluble zinc salt includes one or a combination of two or more of zinc sulfate, zinc chloride, zinc nitrate, zinc acetate, zinc trifluoromethanesulfonate, zinc perchlorate, zinc trifluoromethanesulfonyl imide, and zinc tetrafluoroborate.

3. The aqueous composite electrolyte containing a charge-separating inner salt additive according to claim 1, characterized in that: The concentration of the charge-separating inner salt additive in the aqueous composite electrolyte containing the charge-separating inner salt additive is 0.2-5 mol / kg.

4. The aqueous composite electrolyte containing a charge-separating inner salt additive according to claim 1, characterized in that: The concentration of the soluble zinc salt in the aqueous composite electrolyte containing the charge-separated inner salt additive is 0.2-4 mol / kg.

5. A method for preparing an aqueous composite electrolyte containing an inner salt additive for charge separation, characterized in that: The method comprises the following steps: adding a soluble zinc salt into deionized water to prepare an aqueous zinc salt electrolyte; taking the prepared aqueous zinc salt electrolyte, adding a charge-separated inner salt additive, continuously stirring until completely dissolved, and standing to obtain an aqueous composite electrolyte containing the charge-separated inner salt additive.

6. An aqueous zinc ion battery, characterized in that: An aqueous composite electrolyte comprising the charge-separating inner salt additive according to claim 1.

7. The aqueous zinc ion battery according to claim 6, characterized in that: The battery includes a symmetrical battery assembled from commercial zinc sheets, a half-cell assembled from commercial current collectors, and an aqueous zinc ion battery assembled from a commercial zinc sheet as a negative electrode and a metal oxide as a positive electrode.

8. The aqueous zinc ion battery according to claim 7, characterized in that: The metal oxides include MnO2, NH4V4O 10 , V2O5 or VO2; The commercial current collector is selected from any one of titanium foil, copper foil, nickel foil, stainless steel mesh, copper mesh, nickel mesh, foam copper and foam nickel.